Literature review of vibrotactile systems addressing freezing of gait in parkinsonians - Goncalves, Helena (2017)
Parkinson's Disease is a degenerative neurological disorder of Central Nervous System, which affects the motor and non-motor system and for which there is still no cure. The events of Freezing of Gait are one of the most critical gait impairments and once the medication and the palliative care have not influenced the overcoming of freezing episodes, in the recent years, several non-pharmacological methods have deserved attention. In particular, the vibrotactile feedback systems, have been proven be effective not only in improving the gait of parkinsonians but also in overcoming the freezing episodes Therefore, in this paper, we provide a brief review of the systems and studies performed based in vibrotactile feedback once these methods have proven.